GAMBARAN PELAKSANAAN STANDAR OPERASIONAL PROSEDUR PENGENDALIAN INFEKSI OLEH MAHASISWA PROFESI DI RSGM FKG USAKTI JAKARTA - Aditya Pratama Sarwono (LPPM Universitas Pekalongan, 2019)
Infection is one of the main causes of death in hospitals and other health care facilities. Therefore, infection prevention and control is an effort that must be carried out by every health worker. This study aims to find out the description of the implementation of standard operational procedures for infection control by professional students at RSGM FKG Usakti. This type of research is a scriptive observational study with a cross sectional study design. The results of this study indicate that 100% of professional students know the procedures for doing hand hygiene correctly. 98% of professional students consider immunization / booster important to do to prevent infection. 69% of professional students know the color codes of medical and non-medical waste in waste management. 59% of professional students know the standardization of efforts to prevent cross infection according to WHO. 100% of respondents said that there were infectious and non-infectious rubbish bins in each cubicle. 93% of respondents said there was a box yellow on each cubicle. 48% of respondents said that therewas soap in the sink in each cubicle.